THE LANGUAGE FUNCTION IN ORAL DISCOURSE AT SELL-BUY TRANSACTION IN KLEWER MARKET SURAKARTA AND ITS RELEVANCE AS INDONESIAN LEARNING MATERIALS IN SENIOR HIGH SCHOOL - Henry Trias Puguh Jatmiko; Budhi Setiawan; Edy Tri Sulistyo (Universitas Sebelas Maret, 2017)
The research aims to describe the function of language in Sell-buy transaction in Klewer Market Surakarta which covers instrumental function, regulatory function, representation function, interaction function, individual function, heuristic function, and imajinative function which is fundamental to the theory of MAK Halliday (1973), and relevance to the Indonesian learning materials in Senior High School. The method of the research is descriptive qualitative; The source of the data are taken from the transcript of the sale and purchase dialogue in Klewer Market Surakarta and the Indonesian teacher class x senior high school as the informant; The sampling technique in the research uses purposive sampling, data are collected through observation, recording, and interviews. In the research uses triangulation methods to test the data validity. They are theory of triangulation, source triangulation and informant review. The data are analyzed by using an interactive model ( interactive model analysis). The results of the research obtained that heuristic function dominate the conversation and the form of negotiation between seller and buyer in Klewer market Surakarta can be used as the Indonesian language learning material in senior high school.